VIEW OF HUMAN RIGHTS TOWARDS DISPOSAL OF PEOPLE WITH THE "STATELESS" STATUS IN INDONESIA - CASE STUDY: DANKO NIZAR ZLAVIC - Mochammad Ryanindityo; Agung Sulistyo Purnomo (Jurnal Ilmiah Kajian Keimigrasian, 2019)
The Republic of Indonesia is not a country that ratifies the 1954 Convention relating to the Status of Stateless Persons nor the 1961 Convention on the Reduction of Statelessness, therefore Indonesia does not recognize the term “stateless persons”. As a result, the treatment of stateless persons are carried out by the Indonesian Immigration as like any other illegal immigrants. One example of this stateless persons case is the case of Danko Nizar Zlavic, who was detained for more than fifteen years on the grounds of not having a valid travel document and/ or stay permit in Indonesia due to the absence of citizenship recognition or verification by his foreign representative in Indonesia. This research aims to determine the cause of the foreign representative not acknowledging or recognizing Zlavic as its citizen and to view the case of Zlavic from a human rights perspective.